ANALISIS DETERMINAN INTERNAL YANG MEMENGARUHI PROFITABILITAS BANK-BANK DENGAN ASET TERBESAR TAHUN 2015-2022 - Sitanggang, Yohana Damaris; Wildana, Muhammad Dandy Alif (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Covid-19 had raised concerns among investors, leading to a decline on the stock price. Banks had successfully restored investors confidence by maintaining their profitability. This research aims to see how banks manage internal banking resources to achieve optimal profits by determining the influence of assets, capital, deposits, loans, and Operational Efficiency Ratio (BOPO) on Return on Assets (ROA) of banks during the Covid-19 Pandemic. The data used in this study are Bank BRI, Mandiri, BNI, BCA, BTN, and BSI’s quarterly financial reports from 2015-2022. The research method employed is panel data analysis using random effect model. The result of the analysis indicates that capital and BOPO significantly affect ROA, while assets, loans, and deposits do not significantly influence ROA. Simultaniously, the variables of assets, capital, deposits, loans, and BOPO collectively affect ROA.